The Dynamics of Knowledge in Portugal – The Role Played by Public Institutions - LOPES, Margarida Chagas (Journal of Research in Educational Sciences; Vol 7 No 9 (2016): Journal of Research in Educational Sciences, 2016)
The process of knowledge development in Portugal has progressed at very different speeds in function of the economic outlook and the alternation of political power. The main driving and regulatory forces have been greatly conditioned by domestic and international restrictions. In this framework, public institutions during the previous social-democratic Government and above all the Portuguese Agency for Science and Technology, have greatly contributed to the backlash in the previous favourable evolution which had been characterizing the evolution of knowledge development since the first decade of 2000.This has led to instability and the discontinuity of the framework of public policy, which has been faced with two kinds of fundamental problems: a series of structural blocks which have proved difficult to eradicate, and the lack of a true knowledge strategy.
Keywords: knowledge development, Portugal, political alternation, public institutions, regulation.